Breaking Barriers: Examining Inclusive Education in Islamic Schools through the Merdeka Belajar Curriculum - Khofidotur Rofiah; Farida Isroani; Muhammad Nurrohman Jauhari (SPECIAL: Special and Inclusive Education Journal, 2023)
This study analyses how inclusive education is being implemented in Madrasah in Indonesia through the "Merdeka Belajar" program. The research uses document and content analysis to examine the Decree of Ministry of Religious Affairs of the Republic of Indonesia about guidelines for the implementation of the “Merdeka Belajar” curriculum in madrasahs (KMA RI No. 347 of 2022) policy document as a means to comprehend the intricate essence and origin of the issue, particularly in relation to inclusive education. The study reveals that the policy document mentioned the term diversity, students with disabilities, and inclusive education, however, the terms are limited and still need more specific explanations about inclusive education. The result shows that the "Merdeka Belajar" program is an important initiative that seeks to create inclusive classrooms where all students can receive a quality education in Madrasah setting.